THE INFLUENCE OF MOTIVATION AND COMPENSATION ON EMPLOYEE PERFORMANCE AT PT. BANK CIMB NIAGA, WEST JAKARTA - Lili Sularmi; Veritia Veritia; Feb Amni Hayati (International Journal Management and Economic, 2025)
This study aims to analyze the effect of motivation and compensation on employee performance at PT Bank CIMB Niaga, West Jakarta. The research used a quantitative approach with a survey method through questionnaires distributed to 70 respondents. The independent variables include work motivation, which encompasses responsibility, work achievements, and development opportunities, as well as compensation, which consists of salary, incentives, and allowances. Employee performance, as the dependent variable, was measured through work discipline, loyalty, cooperation, effectiveness, and efficiency. The analysis results show that work motivation has a positive and significant effect on employee performance. Compensation also has a positive and significant effect on employee performance. Simultaneously, motivation and compensation have a significant effect on employee performance. This indicates that 54% of the variation in employee performance can be explained by motivation and compensation. The study concludes that improving motivation and compensation plays an essential role in enhancing employee performance. The company is advised to continue improving the reward system and provide better development opportunities to create a productive work environment that supports the achievement of company goals